The effectiveness of hot in-place recycling technique compared to conventional method [electronic resource] - Siti Nur Hafizeanie Salahuddin, 1980- (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Jalanraya dan Pengangkutan)) - Universiti Teknologi Malaysia, 2007